Profiling saints: images of modern sanctity in a global world - Frei, Elisa; Rai, Eleonora - (Refo500 academic studies, 2023)
“Profiling Saints” follows and expands the papers presented at the homonym online international conference (December 2021), which focused on cultural, theological, artistic, and social aspects of models of sanctity and their importance in the modern world up to the post-revolutionary period. This volume aims thus to shed light on the cultural value of canonizations and models of sanctity as models of Christian perfection, including the role of iconography and artworks, in the broader context of modern, global Catholicism. The topics presented by the authors include veneration to, and canonization and representations of, saint theologians, missionaries, martyrs, mystics, and reformers, men and women. “Profiling Saints” looks at modern sanctity and saints from multidisciplinary perspectives, ranging from liturgy, theology, and Church history up to history of ideas, cultural history, history of emotions, and art history, and contributes to shed light on such a complex phenomenon of Christian history in its modern developments.